IMPERATIVE SENTENCES IN THE NOVEL KITA PERGI HARI INI BY ZIGGY ZESYAZEOVIENNAZABRIZKIE (SYNTACTIC STUDY) - Angeline, Brigita Agnes; Asfar, Dedy Ari; Syahrani, Agus (Indonesian language and literature education program Majapahit Islamic University, 2024)
This study aims to examine the use of imperative sentences in the novel Kita Pergi Hari Ini by Ziggy Zesyazeoviennazabriskie from a syntactic perspective. Imperative sentences, as a form of communication that contains orders, pleas or invitations, can form a narrative significantly in literary works. In the context of this novel, syntactic analysis will explore the structure, pattern, and function of imperative sentences in building the storyline and describing the characters. The analysis method used is a qualitative descriptive approach, with reference to syntax theory. The data collection technique used is a documentary technique. The data analysis technique is carried out by describing and recording the data that has been determined based on the problem to be researched. The data used in this study are sentences, words, or dialogues in the novel Kita Pergi Hari Ini by Ziggy. The results of this research will explain and distinguish imperative sentences in the novel Kita Pergi Hari Ini by Ziggy in the form of imperative sentences of commands, requests, and invitations. This research is expected to provide new insights into the use of imperative sentences in modern literary works as well as contribute a deeper understanding of the novel Kita Pergi Hari Ini by Ziggy Zesyazeoviennazabriskie. Keywords: imperative sentences, novels, syntax